Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Collaborating with Marine Birds to Monitor the Physical Environment Within Coastal Marine Protected Areas - Rachael Orben; Adam Peck-Richardson; Alexa Piggott; James Lerczak; Greg Wilson; Jessica Garwood; Xiaohui Liu; Sabir Muzaffar; Alexa Foster; Humood Naser; Mohamed AlMusallami; Tycho Anker-Nilssen; et al. (Oceanography, 2025)
Animal telemetry is maturing into a viable method for observing the ocean as it can be used to monitor both environmental conditions and biological metrics along the movement trajectories of marine animals. As part of the Cormorant Oceanography Project, we have augmented a biologging tag with an external fast response temperature sensor to collect ocean temperature profiles from the backs of foraging marine birds. Cormorants dive between 50 and 250+ times a day to forage for prey so they can provide hard-to-match temporal and spatial coverage of coastal ocean conditions within their foraging areas. We process tag measurements to obtain fundamental oceanographic data (e.g., temperature profiles, bottom soundings, surface current measurements). Together, we have tracked 17 marine bird species (including two Spheniscus penguins spp. and a sea duck), originating from 17 countries and foraging along the edges of all major oceans. Tagged birds’ distribution included 191 MPAs in 26 countries, offering a unique ocean monitoring method to complement more widely used methods.

Changes in Physicochemical and Microbial Markers on the Storage of a Sweet Sorghum Beverage Treated with Preservatives - Gillian Eggleston; Matthew Heckemeyer; Stephania Imbachi-Ordonez; Alexa Triplett; Chardcie Verret; Tyrenee Foster (Sugar Tech, 2024)

A sea of birds: first bird population assessments in the Saudi Arabian Red Sea - Licia Calabrese; Julie Ann Riordan; Imogen Anne Lloyd; Alexa Darby Foster; Thomas Edward Collier; Johannes Alexandre Chambon; Yasir Wusayl Aljohani; Essa Ali Alhamdi; Patrick Rowan Beaumont; Ivor Douglas Williams; Omar Al-Attas (Frontiers in Marine Science, 2024)
Introduction Seabirds and other insular birds are an important part of marine ecosystems and are increasingly threatened worldwide. Phenology, abundance, distribution, and breeding success are important baseline parameters needed to evaluate population trends and dynamics, identify biodiversity hotspots and potential breeding sites, and assess habitat selection. In the Red Sea basin, reliable and complete data on birds are lacking for islands in most of the Important Bird Areas (IBA). Such data are now especially important since development projects have started at several of these locations. Here, we assess the distribution, abundance, phenology, and population trends of 13 bird species that breed in the Duba Islands, Al Wajh Bank, and Al Lith Islands. Breeding success and habitat selection for six species were also assessed. Methods Between December 2020 and August 2023, more than 90 islands were visited multiple times with different frequencies. All nests were counted, and the area occupied by the different colonies was georeferenced. Breeding success was assessed by visiting selected colonies multiple times until the chicks were ready to fledge. Habitat selection was determined by analyzing the habitat found in the georeferenced colonies. Results More than 25,000 nests were counted each year, mainly in the summer, on more than 75 islands. Of the 13 species studied, the most abundant and widespread species was the White-cheeked tern, and the second most widespread was the Osprey. Discussion We estimate that the Al Wajh Bank hosts the following percentages of global breeding populations: Crab plover: 5%, Sooty gull: 17%–35%, White-eyed gull: 15%, Bridled tern: 1%, White-cheeked tern: 4%, and Lesser crested tern: 2%, making the area a regional and global hotspot for these species. Some of the islands occupied by breeding birds are slated for development for tourism activities as part of the Kingdom’s tourism expansion plans. At the same time, there are several ambitious conservation programs underway in these areas. To be effective, such programs require reliable and comprehensive data of the kind presented here.

Comparison of Composition and Nutritional Characteristics of Sweet Sorghum (Sorghum bicolor L. Moench) and Commercial Vinegars to Aid Their Utilization - Gillian Eggleston; Vitor Teixeira; Giovanna Aita; Alexa Triplett; Chardcie Verret; Tyrennee Foster; Eldwin St. Cyr; Matthew Heckemeyer (Sugar Tech, 2024)